Lignite, dewatered lignite and modified subbituminous coal reduce nitrogen loss from broiler litter. (December 2021) - Costello, Brendon; Chen, Deli; Han, Bing; Zhang, Wei; Butterly, Clayton R.
Graphical abstract: Highlights: The addition of lignite to broiler bedding can reduce nitrogen loss. Aerobic thermal treatment of coal can improve its capacity to reduce nitrogen loss. Ammonia emissions from broiler litter can be reduced using coal amendments. Coal reduced organic nitrogen mineralisation and dry matter loss in broiler litter. Abstract: Broiler litter is generated in large quantities as a waste by-product of chicken meat production. N may be lost from the litter and emitted from bird housing as gaseous NH3, which can be damaging to the environment and limit the recycling of a valuable nutrient. This study investigated the effect of lignite application rate (0, 5, 10, 15, 20%) on N loss from broiler litter in a static chamber laboratory incubation. Lignite was subsequently dewatered and subbituminous coal modified by aerobic thermal oxidation and their ammoniacal N adsorption potentials were characterised. In a second static chamber incubation, the capacity of these materials (applied at 20%) to reduce N loss from litter was investigated. Finally, their potential to directly reduce NH3 emissions was examined using a chamber acid trap system. This study showed that lignite reduced N loss when applied to litter at a rate ≥ 5%, with the amount of N retained increasing with increasing lignite application rate. Litter treated with 20% lignite retained 24% more N than untreated litter. Following aerobic thermal treatment, maximum ammoniacal N adsorption capacities of the materials were as follows: lignite > dewatered lignite > modified subbituminous coal > subbituminous coal. Despite inequalities in adsorption capacity, lignite, dewatered lignite and modified subbituminous coal reduced total N loss by 17.3, 18.2 and 18.4% and NH3 emissions by 41.6, 49.1 and 29.8%, respectively. This study demonstrates the potential of coal-based materials to reduce NH3 emissions from broiler litter and increase the nutrient value of waste by reducing N loss.